Statistical Methods and Computer Applications - Arora, P.N; Guruprasad, N (Himalaya Publishing House, 2009)
Some of the exclusive features of the book are: Every concept has been explained with the help of solved examples. Working rules showing the various steps for the applications of formulae have also been given. The diagrams and graphs have been neatly and correctly drawn in such a way that the students have the complete understanding of the problem by simply looking at them. Efforts have been made to make the subject throughly exhaustive and nothing important has been omitted. Answer to all the problems have been throughly checked. It is a user-friendly book containing many, solved problems and a large number of unsolved questions.